Clean Indoor Air in El Paso, Texas: A Case Study - Jennifer H. Reynolds, MPH; Robin L. Hobart, MPH, MPP; Patricia Ayala; Monica H. Eischen (Centers for Disease Control and Prevention, 2005)
Background Exposure to secondhand smoke is an important preventable cause of illness and death. A Smoke-Free Paso del Norte Coalition in El Paso, Texas, led a drive to introduce an ordinance to protect nonsmoking persons from the health effects of secondhand smoke in public places. The ordinance was introduced in April 2001 and was passed on June 26, 2001. Context El Paso is the fifth largest city in Texas and the largest border city in the United States. It is the 10th poorest city in the United States; 37% of its residents do not have health insurance. Seventy-eight percent of El Pasos residents are Hispanic/Latino. A large percentage of El Pasos restaurant and bar workers are recent immigrants from Mexico. Methods Campaign activities included a letter-writing campaign to the El Paso Times, petition gathering, community outreach education, meetings with city council members, print and television advertising, a proactive media advocacy campaign, and a youth rally. Consequences One month after the ordinance went into effect, an opinion poll found solid support for the new ordinance. Another survey conducted in December 2002 also found a 22% decline in adult smoking, from 22.1% in 1996 to 17.3% at the time of the survey. Interpretation The El Paso campaign is an example of a successful grassroots campaign. El Pasos campaign relied on direct organizing to identify, recruit, and mobilize supporters, and involved relatively little paid media or paid advocacy efforts. These lessons are transferable to other communities, and the El Paso coalition serves as a model for developing a diverse, representative coalition in a predominantly Mexican American community.